Safety and tolerability of navigated TMS for preoperative mapping in neurosurgical patients. Issue 3 (March 2016) - Tarapore, Phiroz E.; Picht, Thomas; Bulubas, Lucia; Shin, Yasushi; Kulchytska, Natalia; Meyer, Bernhard; Berger, Mitchel S.; Nagarajan, Srikantan S.; Krieg, Sandro M.
Highlights: This large, multicenter series describes the safety of pre-operative navigated TMS mapping in 733 neurosurgical patients. Navigated TMS was well-tolerated overall; the median VAS score was 0 with monopulse TMS and 5 with repetitive TMS. The safety profile of navigated TMS in neurosurgical patients was excellent, with no persistent headaches reported and no provoked seizures in the series. Abstract: Objective: Navigated transcranial magnetic stimulation (nTMS) is a non-invasive technique for pre-surgical motor and language mapping in patients with brain lesions. This study examines the safety and tolerability of nTMS in a large, multi-center cohort of neurosurgical patients. Methods: Functional mapping with monopulse and repetitive nTMS was performed in 733 patients. In this cohort, 57% of patients had left-sided tumors, 50% had frontal tumors, and 50% had seizures secondary to the lesion. Side effects and pain intensity related to the procedure were documented. Results: Patients undergoing monopulse stimulation underwent an average of 490 pulses while those undergoing repetitive stimulation received an average of 2268 pulses. During monopulse stimulation, 5.1% reported discomfort (VAS 1–3), and 0.4% reported pain (VAS > 3). During repetitive stimulation, 23.4% reported discomfort and 69.5% reported pain. No seizures or other adverse events were observed. Conclusions: nTMS is safe and well-tolerated in neurosurgical patients. Clinicians should consider expanding nTMS to patients with frequent seizures, but more evaluation is necessary to evaluate this risk fully. Significance: nTMS is safe and well-tolerated, even in neurosurgical patients with persistent occasional seizure secondary to a lesion. It should be considered in any patient with a lesion in a presumed peri-eloquent or eloquent brain region.